The analysis of MMP2, MMP3 and MMP9 matrix metalloproteinases genes polymorphism among Russian Caucasian patients with primary open-angle glaucoma - A.V. Shevchenko; V.F. Prokof’ev; V.I. Konenkov; O.V. Ermakova; A.N. Trunov (Офтальмохирургия)
Relevance. Glaucoma is one of the significant causes of irreversible blindness among aging population around the world. The significant role of matrix metalloproteinases (MMPs) in the remodeling of eye structures during the development of glaucoma is widely discussed in the scientific literature. It is assumed that the polymorphism of the regulatory regions of the genes encoding MMP can affect the level of their expression and contribute to predisposition to the development of the disease. Purpose. To study the features of the polymorphism of the genes of matrix metalloproteinases MMP2, MMP3 and MMP9 in patients with primary open-angle glaucoma. Material and methods. Main group 99 patients with a verified diagnosis of stage II primary open-angle glaucoma. 100 people without glaucoma in anamnesis are included in the control group. Polymorphism of promoter region MMP2 (rs2438650), MMP3 (rs3025058), MMP9 (rs3918242) genes was analyzed. Results. It is shown that minor homozygous genotype MMP2 is significantly more frequent, and heterozygous genotype MMP2 is less frequent among patients with glaucoma. Two complex genotypes which associated with disease were identified. The protective MMP2-1306 TT genotype was confirmed at group of women with glaucoma relative to women without glaucoma and high odds ratio of disease developing for complex genotype MMP2-130 6TC:MMP3-1171 6A6A was shown relative to the general group. Conclusion. The data we obtained on the protective significance of the presence in the human genome of the homozygous variant of the MMP2 gene -1306TT allow us to use them in further studies related to risk of occurrence and development of primary open-angle glaucoma.